PEMBUATAN WEB BASE SIMULATOR PLANT DENGAN PLC UNTUK KULIAH PRAKTIKUM SECARA DARING - Muhamad Anda Falahuddin; MUHAMMAD ARMAN; Farash Arya Pratama; Muhammad Rasyid Ali (KURVATEK, 2020)
The COVID-19 pandemic condition has made lecture activities shift to online lectures. For theoretical lectures, it is relatively easy to do, but for practical activities, facilities are needed in the form of a plant simulator. In this research, create a web-based plant simulator using PLC Logo! Siemens. The initial stage of this process is to create a simulator using the PLC Logo! locally. This simulator draws the relationship of a number of digital inputs and digital outputs, programmed using the logo software! soft. Furthermore, a web base simulator is developed using a web editor, so that the simulator can be accessed through web access by students. The tests carried out include functional testing locally and online device access testing by students. The test results show that the web base simulator plan can be used as an online practicum tool in a limited environmentKeywords: Web server, simulator, PLC